Impact of the SCAMPER Program on the Acquisition and Retention of Physical Education Teaching Method Concepts and the Development of Creative Thinking Skills - Basem, Jamal (Jurnal Ilmiah Sport Coaching and Education, 2025)
ABSTRACT This study investigates the impact of the SCAMPER instructional program on third-year students' comprehension and long-term retention of concepts related to teaching methods in physical education, as well as its influence on the enhancement of creative thinking skills. The research was conducted within the College of Physical Education and Sports Sciences at the University of Mosul during the 2022–2023 academic year. The study population included all third-year students enrolled in the college, from which a randomized sample of 53 students was selected, specifically from sections C and D. Section C served as the experimental group, while section D functioned as the control group. Prior to the intervention, statistical procedures confirmed the equivalence and homogeneity of both groups in variables relevant to the experimental conditions. An experimental methodology was employed, utilizing a pretest-posttest design with equivalent groups to evaluate the outcomes of the intervention. The SCAMPER-based instructional program was implemented over a six-week period, incorporating a range of educational activities structured around the SCAMPER model (Substitute, Combine, Adapt, Modify, Put to Other uses, Eliminate, Reverse). Key findings of the study included the following: (1) The SCAMPER program, when integrated with educational technology, significantly enhanced students’ acquisition of physical education teaching concepts, (2) The program also positively affected the retention of these concepts over time, (3) The intervention contributed to the development of core components of creative thinking among the participants. Keywords: SCAMPER Program, Physical Education, Teaching Method Concepts, Creative Thinking.  ABSTRAK Penelitian ini menyelidiki dampak program pembelajaran SCAMPER terhadap pemahaman siswa tahun ketiga dan retensi konsep jangka panjang yang berkaitan dengan metode pengajaran dalam pendidikan jasmani, serta pengaruhnya terhadap peningkatan keterampilan berpikir kreatif. Penelitian tersebut dilakukan di lingkungan Sekolah Tinggi Pendidikan Jasmani dan Ilmu Olah Raga Universitas Mosul pada tahun ajaran 2022–2023. Populasi penelitian mencakup seluruh siswa tahun ketiga yang terdaftar di perguruan tinggi, dari mana sampel acak sebanyak 53 siswa dipilih, khususnya dari bagian C dan D. Bagian C berfungsi sebagai kelompok eksperimen, sedangkan bagian D berfungsi sebagai kelompok kontrol. Sebelum intervensi, prosedur statistik memastikan kesetaraan dan homogenitas kedua kelompok dalam variabel yang relevan dengan kondisi eksperimen.Metodologi eksperimental digunakan, memanfaatkan desain pretest-posttest dengan kelompok setara untuk mengevaluasi hasil intervensi. Program pengajaran berbasis SCAMPER dilaksanakan selama periode enam minggu, menggabungkan berbagai kegiatan pendidikan yang terstruktur berdasarkan model SCAMPER (Pengganti, Penggabungan, Adaptasi, Modifikasi, Penggunaan Lain, Penghapusan, Pembalikan). Temuan-temuan utama dari penelitian ini mencakup hal-hal berikut: (1) Program SCAMPER, ketika diintegrasikan dengan teknologi pendidikan, secara signifikan meningkatkan perolehan konsep-konsep pengajaran pendidikan jasmani oleh siswa, (2) Program ini juga berdampak positif terhadap retensi konsep-konsep ini dari waktu ke waktu, (3) Intervensi ini berkontribusi pada pengembangan komponen inti pemikiran kreatif di antara para peserta. Kata Kunci: Program SCAMPER, Pendidikan Jasmani, Metode Pengajaran Konsep, Berpikir Kreatif.